(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2016)
Background: Psychological distress has become an epidemic among cancer patients. Less is known about the pattern of anxiety and depression in cancer patients with minor children. Gender issue is also important in this regard. Psychological distress is an important predictor of quality of life in cancer patients. A majority of these disorders are eminently treatable. Materials and methods: A cross-sectional comparative study was done to compare anxiety and depression status between cancer patients having and not having minor children, attending at National Institute of Cancer Research Hospital, Oncology department in Dhaka Medical College Hospital and in Uttara Adhunik Medical College Hospital. The study was conducted for the time period from September, 2012 to June, 2013. In study group, having underage children, 123 cancer patients were included. Whereas in comparison group without having underage children, 116 patients were selected. Purposive sampling was applied. Cancer patients in both groups were selected randomly, each between the age from 20 to 60 years, corresponding to Karnofsky Performance Scale Score > 79. All The included cancer patients were married and did not have history of substance use or any prior psychiatric illness or co morbidities related to development of secondary psychiatric disorders. Distress among the patients were measured with the Hospital Anxiety and Depression Scale (Two sub scales A Anxiety subscale and D Depression subscale). Result: In the study group, 60.2% respondents was male and 39.8% was female. And in comparison group male and female ratio was 42.2% and 57.8%. Mean age of the participants in study group was 36.97±4.37 and in comparison group was 42.98±11.74 years respectively. The mean duration since diagnosis was 12.85±13.11 months in study group and 11.53±6.72 months in comparison group. Majority of the respondents in study group were suffering from guynaecological cancer (25.2%) and gastro intestinal cancer (25.2%). Whereas majority cancer patients in comparison group were guynaecological cancer (31%) and haematolymphoid cancer (20.7) as well. Metastasis was present in 42.3% patients in study sample and 64.7% patients in comparison group. It was noticed that, both male and female in study group were found significantly more distressed than the comparison group (p < 0.001). In study group mean anxiety score in male (n=74) was 15.72±2.314 and in female (n=49) was 12.06±2.802, i.e. father with minor children were suffering from more anxiety than the mother (t = 7.878, p < 0.001). Mean depression score in male (study group) was 11.91±2.489, whereas in female it was 17.55±2.542, i.e. female cancer patients with minor children were found more depressed than male (t = 12.211; and p < 0.001). In comparison group, mean anxiety score among male (n=49) was 7.27±1.630 and in female (n=67) mean anxiety score was 8.84±1.592. Female were more anxious than male in comparison group (t = 5.196; p < 0.001). In this group, mean depression score in male was 9.671±1.651 and in female it was 8.58±2.161. Male without minor children were found more depressed than female in this group (t = 2.958; p = 0.004). But among all the cancer patients majority of female were found anxious (93.1%) i.e prevalence of anxiety was more in female. And majority of the male respondents (95.1%) were depressed; (odds ratio; depression in male: female = 3.120; CI at 95% level from 1.176 to 8.276). Conclusion: Cancer father with minor children were more prone to development of higher anxiety. And anxiety was more prevalent in female among all the cancer patients with and without minor children. J. Paediatr. Surg. Bangladesh 6(1): 10-15, 2015 (Jan)